Pengaruh Pembinaan Manajemen Usaha Terhadap Kinerja Usaha Mitra Binaan PKBL PT Jasa Marga - Mudjiarto, Mudjiarto (Lembaga Penerbitan Unversitas Esa Unggul, 2014)
This study contains the analysis ofthe effect of training, the Old Business and Education Levels of Business Performance Partners PT Jasa Marga. Business performance measurement indicatorsare based on the number of criteria achieved in the management of business partners include human resource management, production, administration, finance,marketing and business motivation.The purpose of the studyis to determine the exact pattern of development by looking at the business performance of SMEs. From the results of the data kolekting results of training and supervision of the partners of PT Jasa Marga Jagorawi Branch, Cikampek, Tangerang and CTC shows that research data were analyzed by regression and ANOVA for the variable value of training, business experience, Level of Education and Business Performance Partners found that: (1)The difference in performance Influence on Education Level Partner. Business Performance partner increases with level of education. Business Performancein theaverage value of a group of elementary and junior highat 4.34; SMU4.47; Graduate Diploma of 4.87 and 4.89 for, (2)The mean difference Influence on Business Performance Business Experience. Business Performance increases with the old partners' business experience. Average Business Performance obtained in the group under 2 years of business experience 3.87; on the business experience of 2 to 5 years of 4.54; on the business experience of 5 to8 years by 4.73; and the busines sex perience of over 8 yearsis equal to 5.02; (3)Regression test result sindicate that the magnitude of the effect of variables on Business Performance Training partners are value(X1) is positive at75.9%, Business Experience (X2) 21.2% positive and Education Partners (X3) of 26.6 positive for mregression model.Y=0.866+0.212+0,759X1X2+0.266 Keywords: training, development, partnership AbstrakPenelitian ini berisikan analisa pengaruh Pelatihan, Lama Usaha dan Tingkat Pendidikan Mitra terhadap Kinerja Usaha Mitra Binaan PKBL PT Jasa Marga.Indikator pengukuran Kinerja Usaha didasarkan pada banyaknya kriteria yang dicapai mitra pada manajemen usaha meliputi pengelolaan sumberdaya manusia, produksi,administrasi keuangan, pemasaran dan motivasi usaha.Tujuan penelitian adalah menentukan pola pembinaan yang tepat dengan melihat kinerja usaha dari UMKM..Dari hasil kolekting data hasil pelatihan dan supervisi mitra binaan PT Jasa Marga Cabang Jagorawi, Cikampek, Tangerang dan CTC menunjukkan Data penelitian yang dianalisa melalui uji regresi dan Anova untuk variabel Nilai Pelatihan, Pengalaman Usaha, Tingkat Pendidikan dan Kinerja Usaha Mitra didapat bahwa: (1)adanya perbedaan Pengaruh Kinerja pada Tingkat Pendidikan Mitra. Kinerja Usaha mitra meningkat sebanding dengan tingkat pendidikan. Nilai rerata Kinerja Usaha pada kelompok SD-SMP sebesar sebesar 4,34; SMU sebesar 4,47; Diploma sebesar 4,87 dan Sarjana sebesar 4,89, (2)adanya perbedaan Rerata Pengaruh Kinerja Usaha pada Pengalaman Usaha. Kinerja Usaha mitra meningkat sebanding dengan lama pengalaman usaha. Rerata Kinerja Usahayang didapat pada kelompok pengalaman usaha dibawah 2 tahun sebesar 3,87; pada pengalaman usaha 2 sampai 5 tahun sebesar 4,54; pada pengalaman usaha 5 sampai 8 tahun sebesar 4,73; dan pada pengalaman usaha diatas 8 tahun adalah sebesar 5,02;, (3)Hasil uji regresi menunjukkan bahwa besaran pengaruh variabel terhadap Kinerja Usaha mitra adalah Nilai Pelatihan (X1) positif sebesar 75,9 %, Pengalaman Usaha (X2) positif sebesar 21,2 % dan Pendidikan Mitra (X3) positif sebesar 26,6 membentuk model persamaan regresi Y = 0,866 +0,759X1+0,212 X2+0,266 Kata kunci: pelatihan, pembinaan, kemitraan